Studi Dinamika Bakteri Dan Kualitas Air Selama Proses Awal Bioflok - Andi Kurniawan; Citra Satrya Utama Dewi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2018)
Bioflok is a relatively new technology in the field of aquaculture. The weakness of this technology is the need that takes a long time. This ultimately decreases the task and waiting period for fish production. This study aims to analyze the dynamics of air quality and bacteria that will be used as a basis for making rapid biofloc technology. The research was conducted by examining air quality, physics, and chemistry. The results show that the sidika chemical (DO, temperature, pH, intelligence, air color) parameters are not always significant which occurred for eleven days. While the dominant bacteria are the bacteria genus Bacillus, Lactobacillus and Nitrosomonas. This shows that early biofilm formation with these bacteria.